Effects of Nebivolol on Aortic Compliance in Patients With Diabetes and Maximal Renin Angiotensin System Blockade: The EFFORT Study. Issue 7 (30th April 2013) - Briasoulis, Alexandros; Oliva, Raymond; Kalaitzidis, Rigas; Flynn, Colleen; Lazich, Ivana; Schlaffer, Carrie; Bakris, George
<x xml:space="preserve">Abstract</x> The beneficial effects of nebivolol on arterial stiffness and endothelial dysfunction are well documented in untreated hypertensive patients and differ from nonvasodilatory β‐blockers. This study tests the hypothesis that the addition of nebivolol in predominantly African American patients with type 2 diabetes already receiving maximally tolerated doses of renin‐angiotensin system (RAS) blockers will further improve large artery compliance. Patients with type 2 diabetes and hypertension on maximal RAS blockade (n=70) were randomized to nebivolol or metoprolol succinate daily. Doses were titrated until systolic blood pressure (SBP) was <130 mm Hg. Radial artery applanation tonometry and pulse wave velocity (PWV) analysis were used to derive central aortic pressures and hemodynamic indices at repeated visits at intervals during a 6‐month period. Both metoprolol succinate and nebivolol groups demonstrated reductions in brachial SBP (−8.2±4.3 mm Hg [P=.01] and −7.8±3.7 [P=.002], respectively) and aortic DBP (−2.4±1.8 [P=.039] and −4.0±2.9 mm Hg [P=.013], respectively). Aortic SBP decreased in the nebivolol group only (125.3±8 to 121.6±8.2, P=.025). There were no between group differences in aortic SBP, DBP, augmentation index, or PWV reduction. A significant increase in hemoglobin A1c was observed only in the metoprolol group. In patients with well‐controlled type 2 diabetes and hypertension treated with maximally tolerated RAS blockade, nebivolol does not offer significant reductions in aortic BP over metoprolol succinate but maintains a stable metabolic profile.